Low-dose mRNA-1273 COVID-19 vaccine generates durable memory enhanced by cross-reactive T cells - Mateus, Jose; Dan, Jennifer M; Zhang, Zeli; Rydyznski Moderbacher, Carolyn; Lammers, Marshall; Goodwin, Benjamin; Sette, Alessandro; Crotty, Shane; Weiskopf, Daniela (Science (American Association for the Advancement of Science), 2021)
Vaccine-specific CD4 T cell, CD8 T cell, binding antibody, and neutralizing antibody responses to the 25-μg Moderna messenger RNA (mRNA)–1273 vaccine were examined over the course of 7 months after immunization, including in multiple age groups, with a particular interest in assessing whether preexisting cross-reactive T cell memory affects vaccine-generated immunity. Vaccine-generated spike-specific memory CD4 T cells 6 months after the second dose of the vaccine were comparable in quantity and quality to COVID-19 cases, including the presence of T follicular helper cells and interferon-γ–expressing cells. Spike-specific CD8 T cells were generated in 88% of subjects, with equivalent memory at 6 months post-boost compared with COVID-19 cases. Lastly, subjects with preexisting cross-reactive CD4 T cell memory exhibited stronger CD4 T cell and antibody responses to the vaccine, demonstrating the biological relevance of severe acute respiratory syndrome coronavirus 2–cross-reactive CD4 T cells.